THE COMPRESSIVE STRENGTH CHARACTERISTICS OF THE MASONRY BLOCK FROM THE OIL PALM SHELL - Agus Setyo Muntohar, Muhammad Ekhlasur Rahman (Fakultas Teknik UMS, 2011)
Indonesia and Malaysia is the two largest producer of palm oil. However, one significant problem in the processing of palm oil is the large amounts of waste produced and this is one of the main contributors to the nation’s pollution problem. This paper presents the investigation of the use of oil palm shell waste as masonry block materials. The study was focused on the compressive strength and the durability. The masonry block was made by mixing the portland cement, sand, and oil palm shell waste. The specimen size was 220 mm in length x 110 mm in width x 80 mm thickness. The test results showed that the maximum strength was obtained by mixing proportion of 1 PC : 1 sand : 1 OPS. Addition a large amount of OPS was lowering the compressive strength. Overall results indicated that the shellcrete complied the specification standard for lightweight to medium concrete building brick which was suitable for load bearing purposes.